Advanced theoretical-applied model based on the PD approach in the light of healthcare-associated infections: what have we achieved so far? - Cohen, Ricky; Gesser-Edelsburg, Anat (Frontiers in Public Health, 2024)
Healthcare-associated infections remain a persistent concern despite decades of research and intervention efforts. Adherence to infection prevention and control guidelines by health professionals remains a challenge, necessitating innovative strategies. The Positive Deviance (PD) approach, rooted in harnessing localized solutions, holds promise but lacks comprehensive frameworks and empirical validation to bolster its theoretical underpinnings. This perspective article serves a dual purpose: first, to examine the unique challenges of applying the PD approach in the context of HAIs; and second, to introduce a robust theoretical-applied model developed in response to these challenges. This article addresses these gaps through a multi-faceted model developed in a mixed-methods study across three Israeli governmental hospitals and comprises four essential components that address the identified gaps in existing research. This article enriches the dialog on PD’s applicability in HAIs by providing a robust model that not only offers solutions but reshapes the approach to healthcare hygiene and safety. It responds to critical gaps highlighted in the literature, offering tailored interventions by practical, context-specific solutions to improve adherence to IPC guidelines in the long term. Methodological clarity is also a key focus, offering a toolkit for practical implementation. This bottom-up approach empowers HPs to drive change, fostering a culture of innovation and improvement in healthcare settings.